Chronic inflammatory demyelinating polyradiculoneuropathy: a prevalence study in south east England. Issue 5 (1st May 1999) - Lunn, M P T; Manji, H; Choudhary, P P; Hughes, R A C; Thomas, P K
Abstract : Although there are now widely accepted diagnostic criteria for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) there are few epidemiological data. A prevalence study was performed in the four Thames health regions, population 14 049 850. The prevalence date was 1 January 1995. Data were from a national consultant neurologist surveillance programme and the personal case series of two investigators. A diagnosis of CIDP was made according to definite, probable, possible, or suggestive diagnostic criteria. A wide difference in prevalence rates between the four health regions was noted, probably due to reporting bias. In the South East Thames Region, from which the data were most comprehensive the prevalence for definite and probable cases was 1.00/100 000; the highest total prevalence (if possible and suggestive cases were included) would have been 1.24/100 000. On the prevalence date 13% of patients required aid to walk and 54% were still receiving treatment.